Effects of some parameters on poly ε-caprolactone electrospun fibers produced by the KKU drum electrospinning unit - Chaisri, Patcharaporn; Thomas, Ian; Siri, Sineenat (Asia-Pacific Journal of Science and Technology, 2017)
The “homemade” KKU drum electrospinning unit was constructed to replace the high cost and imported electrospinning apparatus. However, fabrication and parameters affecting the fibers have not yet been studied. Thus, in this work, poly(ε-caprolactone) was used as a model polymer to study the effect of some parameters on morphology and sizes of fibers, including polymer concentrations (4, 8, 10 and 15%), flow rates (0.8, 1, 1.5, 2 and 3 มล./ชม.), voltages (4, 8, 10 and 13 kV) and drum rotation rates (0, 65, 88 and 110 rpm). Results showed that the concentration at 4% was too low and could not form fiber. Increased concentrations and flow rates resulted in increasing fiber sizes. Increased voltages could reduce bead sizes and form more homogeneous fibers. Fiber sizes tended to decrease and become more organized when increasing voltages were applied. The optimized condition to fabricate poly(ε-caprolactone) fiber was at 10% concentration, 0.8 มล./ชม. flow rate, 13 kV voltage and 110 rpm rotation rate.